Vigor de sementes de soja e desempenho da cultura - Silva, Clarissa Santos da (2010)
This work aimed to evaluate soybean seeds cultivated isolated and communities of different arrangements from seeds of high and low vigor, in different population of plants. The experiment was conducted at the Área experimental e Didática da Faculdade de Agronomia Eliseu Maciel using two lots of BRS243 soybean cultivar of different quality. On the first work it was evaluated the effect of seeds vigor on isolated plants, cultivated in hollows of 50 cm of spacing. Two treatments were tested: plant from seeds of high and low vigor, being each parcel composed by one plant. The second one evaluated the individual behavior inside the communities, as well as the entire community behavior in different systems of plants distribution originated from high and low vigor seeds, along the sowing line in different populations. The treatments constituted three arrangements of seeds distribution of high and low vigor along the line sowing and four population of plants (150.000, 300.000, 450.000 e 600.000 plants per hectare). The two treatments were obtained from seed lots with 90% of germination and 81% of accelerated aging, considered high physiological quality, and another one with 79% of germination and 68% of accelerated aging, considered low physiological quality. Soybean plants originated from high vigor seeds present high performance than plants from low vigor seeds, showing a yield above 30%. Plants originated from seeds of high physiological quality showed dominant behavior over the plants from seeds of low physiological quality when arranged adjacent in the line sowing. The population of plants did not affect the competitive effects between the plants from seeds of high and low physiological quality.